Tinjauan Penerapan Sistem Automasi Dalam Pengatalogan Bahan Pustaka di Perpustakaan Universitas Andalas - Rahmayanti, Yusfebry; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of this study is to describe the application of automation systems in library cataloging materials in the Library of the University of Andalas. This type of research is a qualitative descriptive method, which describe the data relating to the implementation of the automation system library cataloging materials in the Library of the University of Andalas. To obtain the data used several instruments, namely observation and interview guides. The findings of the study is the application of automation to cataloging library materials not maximized because the computer often suffer damage to its hardware, data book yet fully recorded in the computer, the amount of hardware is less when compared to the amount of data library materials, management automation are not maximized in distributing data to circulation and OPAC, and the number brainware make fewer librarians work slow.